PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS GURU PADA SEKOLAH DASAR SWASTA KATOLIK DI WILAYAH JAKARTA PUSAT - Hermania Bhoki (Jurnal Manajemen Pendidikan, 2015)
The objective of this research was to understand the effect of Leader Member Exchange (LMX and job satisfaction on productivity. It was a quantitative research was conducted in sixteen schools located in Jakarta Centre . The research uses a survey method with path analysis was applied in testing hypothesis. It was conducted to 153 Teachers at Private Catholic Elementary Schools as the respondents which were selected in a simple random way. The result of this study are: (1). There is a positive direct effect of Leader Member Exchange (LMX) on productivity. (2). There is a positive direct effect of job satisfaction on productivity, and (3). There is a positive direct effect of Leader Member Exchange (LMX) on job satisfaction.